Elucidating the effect of enzymatic polymerized polysaccharide particle morphology on emulsion properties. (1st January 2021) - Kedzior, Stephanie A.; Cranmer-Smith, Sierra; Behabtu, Natnael; Kim, Kyle; Lenges, Christian; Bryant, Steven L.; Trifkovic, Milana
Abstract: Exploiting the shape of Pickering stabilizers offers the ability to unlock the full potential of nanoparticle-stabilized emulsions for applications in enhanced oil recovery, pharmaceuticals, cosmetics, and coatings. In this work, we utilize engineered polysaccharide particles derived from the enzymatic polymerization of glucose from sucrose with controlled shape for the stabilization of dodecane-in-water emulsions. Altering the particle shape (spherical aggregates, fibrids, or platelets), while maintaining a neutral surface charge allows for a systematic examination of the role of particle shape in the stabilization of emulsions. We find that platelet-shaped particles reduce the interfacial tension and result in the smallest droplet size, while emulsions stabilized by aggregates and fibrids are governed by a network of particles in the continuous phase. Exploiting the synergy between these particles allowed for the tuning of their microstructure and rheological signature which allows us to map and tailor these emulsions for a wider variety of applications.